Disparities in assessments of asthma control between children, parents, and physicians. Issue 10 (25th October 2013) - Shefer, Galit; Donchin, Milka; Manor, Orly; Levy‐Hevroni, Revital; Schechter, Abraham; Cohen, Rinat; Cohen, Herman A.; Kerem, Eitan; Engelhard, Dan
Summary Objective Assessment of asthma control in children by physicians, patients and their parents was compared, assuming parents may underestimate symptoms in asthmatic children and exploring whether physicians tend to agree with them. Design Asthma control perception was assessed in 4‐ to 11‐year‐old asthmatic children and their parents, using C‐ACT, during 2011–2012. Pediatric pulmonologists used GINA guidelines for their assessment; pediatricians, not having spirometry, used the information given in addition to physical examination. The C‐ACT scores given by the children and their parents were further analyzed separately, and compared with their physicians' assessment. Statistical methods, which also measured possible influence of different variables, included kappa, Chi‐square, linear‐by‐linear association, McNemar test and logistic regression. Patient Selection The study comprised 354 parents and children aged 4–11 years with moderate‐severe asthma; 129 (36.4%) were treated by 23 pediatricians; 225 (63.6%) by 11 pediatric pulmonologists. Results The C‐ACT was generally found valid in assessing asthma control (P < 0.001; κ 0.529; CI 0.441, 0.617) and showed that in 229/354 (53%) of children the asthma was uncontrolled. Nevertheless, of the 229 children who indicated their asthma was uncontrolled, 124 (54.1%) of their parents (κ 0.245; CI 0.15, 0.34) and 96 (41.9%) of their physicians believed it to be controlled (κ 0.331; 0.24, 0.43). Comparing the physician‐child discordance vis‐à‐vis the parents, the significant difference was when 96/229 children (41.9%) and 34/126 parents (27.0%) indicated the asthma was uncontrolled while the physician determined it controlled (OR 1.95; 1.19, 3.24). There were no significant differences between pediatric pulmonologists and pediatricians. Conclusions In addition to increasing awareness of parents to symptoms in their asthmatic children, physicians should question the child appropriately, as well as using the children's responses to C‐ACT as an information source for properly assessing asthma control. Pediatr Pulmonol. 2014; 49:943–951. © 2013 Wiley Periodicals, Inc.